Perceptions of corruption by perpetrators: An empirical analysis of the fraud triangle and attribution theories - Warsito Kawedar; Rr. Sri Handayani; Milawati (Problems and Perspectives in Management)
Corruption is one of the major challenges facing both developed and developing countries, which seriously undermines governance and economic stability. This is specifically true for civil servants, whose vulnerability to corruption is greatly increased by the particular pressures and opportunities arising in their work. This study aims to explore perceived corruption among civil servants in Semarang, Indonesia, using the fraud triangle and attribution theories that point to psychological and organizational factors in corruption. The sample consisted of 99 civil servants convicted of corruption. This study used multiple linear regression to analyze data on how perceived pressure, opportunity, and rationalization contribute to unethical behavior. From the results, perceived pressure, especially financial stress, and the opportunity for corruption due to weak organizational controls were significant driving factors for corrupt actions. Financial pressure emerged as the most influential factor, followed by the opportunity for unethical behavior in weak organizational environments. The study emphasizes the need to address both psychological factors, such as personal values and ethical leadership, and organizational factors, like strengthening internal controls and reducing opportunities for misconduct. These findings provide valuable messages for policymakers in designing comprehensive anti-corruption strategies that could reduce both internal motivations and external opportunities that foster corruption among civil servants.